IMPROVING THE AUDIT OF MATERIAL COST ACCOUNTING IN MODERN ENTERPRISES: AN IMRAD-BASED STUDY - Fattoyev Orzujon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Material costs make up a large share of total production expenses and strongly influence product prices, profitability, and overall financial stability. When material cost accounting is weak or audit procedures are ineffective, enterprises face higher risks of errors, inefficiencies, and even fraud. This study explores common problems in auditing material cost accounting and suggests practical ways to improve audit quality. Using analytical and comparative methods, the research reviews internal control systems, audit practices, and the growing role of digital technologies. The findings show that risk-based auditing, stronger internal controls, and automated systems significantly improve the accuracy and transparency of material cost information, helping managers make better decisions and use resources more efficiently.